Cellular proliferation and differentiation induced by single-layer molybdenum disulfide and mediation mechanisms of proteins via the Akt-mTOR-p70S6K signaling pathway. Issue 6 (3rd July 2017) - Zou, Wei; Zhang, Xingli; Zhao, Mengyang; Zhou, Qixing; Hu, Xiangang
Abstract: Single-layer molybdenum disulfide (SLMoS2 ) is a novel kind of 2D nanosheet that has attracted great attention regarding its use in biosensors, drug delivery, tissue engineering, and therapy. However, our results demonstrated that SLMoS2 accelerated proliferation and promoted myogenic differentiation and epithelial–mesenchymal transition (EMT) in human embryonic lung fibroblasts (HELFs). The abnormal proliferation and differentiation of HELFs contribute to idiopathic pulmonary fibrosis. Specifically, SLMoS2 significantly stimulated the expression of myofibroblast- and mesenchymal-associated genes and proteins. The Akt-mTOR-p70S6K signaling pathway plays a critical role in the acceleration of proliferation and promotion of myogenic differentiation and EMT in HELFs induced by SLMoS2 . After cell uptake, SLMoS2 was primarily located in the cytoplasm and the perinuclear region and activated Akt-dependent signaling due to the generation of reactive oxygen species (ROS). Moreover, bovine serum albumin (BSA) binding markedly inhibited the cellular uptake of SLMoS2 and the production of intracellular ROS due to an increased thickness and reduced adhesion of HELFs. BSA binding also mitigated the SLMoS2 -activated phosphorylation of Akt-dependent signaling pathways. This study is the first to illustrate the induction of cellular proliferation and differentiation by SLMoS2 and the related mediation by proteins through Akt-mTOR-p70S6K signaling pathway.